EFFECTS OF SMOKE TREATMENT WITH Xylopia aethiopica AND Tetrapleura tetraptera FRUITS ON THE QUALITY OF DRINKING WATER IN ILLAH COMMUNITY, DELTA STATE, NIGERIA (2015)
Water-borne diseases, caused largely by lack of potable water, are among the leading causes of morbidity and mortality. Several indigenous water treatment methods have been developed to enhance the quality of drinking water. In Illah, a combination of dried fruits of Xylopia aethiopica and Tetrapleura tetraptera are used for household treatment of water without information on its potency in water purification. There is no documented information on the effectiveness of this treatment method in reducing level of water contaminants. This study was therefore designed to determine the effects of treatment with Xylopia aethiopica and Tetrapleura tetraptera fruits on the quality of drinking water in Illah community, Delta State, Nigeria. Samples of water from borehole and stream were collected using separate sterile containers in the community. The samples were divided into two parts and baseline analysis was conducted to determine pH, nitrate, iron, lead and Total Coliform Count (TCC) using standard methods. Ten litres of the water sample was left as control while the other 10 litres of water sample was subjected to indigenous water treatment as being practised in the households. In this indigenous water treatment method, 50g dried fruits each of Xylopia aethiopica and Tetrapleura tetraptera were ground together and burnt with hot charcoal thus, producing smoke. The sterile container was faced upside down directly to the smoke for 10 minutes after which the other ten litres of water sample left for treatment was immediately poured into the container. Samples of the treated water were then collected within 24 hours from the container for analyses. Results obtained for pH, nitrates, iron, zinc, lead and TCC were compared with the WHO guideline limits of 6.5-8.5, 50.0 mg/L, 0.3 mg/L, 3.0 mg/L, 0.01 mg/L and 10.0 cfu/mL respectively. Data were analysed using descriptive statistics and t-test at p=0.05. The pH, nitrates, iron, zinc, lead values for borehole water at baseline and after treatment were: 6.5±0.1 and 6.6±0.1, 20.2±0.2 and 20.3±0.9 mg/L, 0.2±0.01 and 0.1±0.03 mg/L, 0.04±0.01 and 0.01±0.004 mg/L, 0.007±0.0001 and 0.004±0.002 mg/L and for stream water at baseline and after treatment were: 6.2±0.2 and 6.3±0.2, 22.2±1.2 and 21.9±0.8 mg/L, 0.3±0.02 and 0.2±0.05 mg/L, 0.01±0.004 and 0.04±0.003 mg/L, 0.009±0.001 and 0.004±0.003mg/L respectively. These values were within the WHO limits for potable water. However, TCC for borehole (129.0±7.8 cfu/mL) and stream (280.0±95.3 cfu/mL) water exceeded the guideline limits. After treatment, TCC for borehole water was 67.0±11.0 cfu/mL showing a significant difference when compared with baseline. The treatment reduced TCC in the borehole by 48.0%. The TCC for treated stream water was 203.0±54.9 cfu/mL. The treatment thus, reduced TCC in the stream water by 28.0%. Treatment of water with Xylopia aethiopica and Tetrapleura tetraptera dried fruits reduced the total coliform counts in both borehole and stream water. However, the total coliform counts were higher than the recommended guideline limits for potable water. An alternative water treatment that is more effective should be sought in the community.